2014
DOI: 10.1063/1.4868364
|View full text |Cite
|
Sign up to set email alerts
|

Universality and scaling phenomenology of small-scale turbulence in wall-bounded flows

Abstract: The Reynolds number scaling of flow topology in the eigenframe of the strain-rate tensor is investigated for wall-bounded flows, which is motivated by earlier works showing that such topologies appear to be qualitatively universal across turbulent flows. The databases used in the current study are from direct numerical simulations (DNS) of fully developed turbulent channel flow (TCF) up to friction Reynolds number Re τ ≈ 1500, and a spatially developing, zero-pressure-gradient turbulent boundary layer (TBL) up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 28 publications
7
24
1
Order By: Relevance
“…This has been observed before by Meinhart and Adrian, 17 Adrian et al, 18 Christensen and Adrian, 23 Hambleton et al, 21 and Wei et al 25 From the analysis performed in Sec. V, we derived the entrainment velocities of conditionally averaged shear layers.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This has been observed before by Meinhart and Adrian, 17 Adrian et al, 18 Christensen and Adrian, 23 Hambleton et al, 21 and Wei et al 25 From the analysis performed in Sec. V, we derived the entrainment velocities of conditionally averaged shear layers.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, it turns out that layered structures were found to be characteristic of the mean structure associated with the principal strain in different turbulent flows by Elsinga and Marusic, 24 which therefore can be considered to be typical for turbulent flow fields. Wei et al 25 have shown that the flow around the shear layers in a TBL exhibits a scaling related to the macro-scales in a TBL. This indicates that the shear layer is closely related to large scales present in the flow.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it extends a similar analysis by Wei et al (2014) for inhomogeneous, anisotropic wall-bounded turbulence by (i) considering a different turbulent flow and (ii) considerably expanding the Reynolds number range, hence scale separation. The flow velocity associated with the local strain is examined at different turbulent length scales ( § 3.1).…”
mentioning
confidence: 85%
“…The flow velocity associated with the local strain is examined at different turbulent length scales ( § 3.1). The comparison with the results obtained by Wei et al (2014) allows assessing of the similarity in the Reynolds number scaling between the different flows, which may reveal quantitative universality (compared to the qualitative similarity in flow pattern observed before, Elsinga & Marusic 2010). Furthermore, the scaling of vorticity and dissipation within the shear layer is considered ( § § 3.2-3.3), from which a coherence length for the small scales is defined.…”
mentioning
confidence: 99%
See 1 more Smart Citation